Human Subthalamic Nucleus in Movement Error Detection and Its Evaluation during Visuomotor Adaptation - Tan, Huiling; Zavala, Baltazar; Pogosyan, Alek; Ashkan, Keyoumars; Zrinzo, Ludvic; Foltynie, Thomas; Limousin, Patricia; Brown, Peter (The Journal of neuroscience, 2014)
Monitoring and evaluating movement errors to guide subsequent movements is a critical feature of normal motor control. Previously, we showed that the postmovement increase in electroencephalographic (EEG) beta power over the sensorimotor cortex reflects neural processes that evaluate motor errors consistent with Bayesian inference (Tan et al., 2014). Whether such neural processes are limited to this cortical region or involve the basal ganglia is unclear. Here, we recorded EEG over the cortex and local field potential (LFP) activity in the subthalamic nucleus (STN) from electrodes implanted in patients with Parkinson's disease, while they moved a joystick-controlled cursor to visual targets displayed on a computer screen. After movement offsets, we found increased beta activity in both local STN LFP and sensorimotor cortical EEG and in the coupling between the two, which was affected by both error magnitude and its contextual saliency. The postmovement increase in the coupling between STN and cortex was dominated by information flow from sensorimotor cortex to STN. However, an information drive appeared from STN to sensorimotor cortex in the first phase of the adaptation, when a constant rotation was applied between joystick inputs and cursor outputs. The strength of the STN to cortex drive correlated with the degree of adaption achieved across subjects. These results suggest that oscillatory activity in the beta band may dynamically couple the sensorimotor cortex and basal ganglia after movements. In particular, beta activity driven from the STN to cortex indicates task-relevant movement errors, information that may be important in modifying subsequent motor responses.